2004
DOI: 10.1262/jrd.50.29
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation and Sexing of <i>In Vivo</i>- and <i>In Vitro</i>-Produced Bovine Embryos for Their Practical Use

Abstract: Abstract. My research awarded includes contributions to cryopreservation and sexing of bovine embryos produced in vitro and in vivo, as follows; (1) In vivo-derived morulae and blastocysts were cryopreserved in the presence of 10% glycerol, and the embryos were transferred into recipients after two-step dilution of glycerol in straw, with a practically acceptable pregnancy rate. (2) The survival rate of 16-cell stage embryos frozen in the medium with ethylene glycol was higher than that with DMSO or 1,2-propan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 49 publications
1
19
0
4
Order By: Relevance
“…There are various reports of livestock pregnancy rates of 30% to 60% when using biopsied embryos, similar to the rates obtained with intact embryos and considered sufficient for commercial applications (Agca et al, 1998, Chrenek et al 2001, Garcia, 2001, Lopes et al 2001, Park et al 2001, Chen et al 2002, Tominaga, 2004, Tominaga and Hamada, 2004.…”
Section: Introductionmentioning
confidence: 64%
“…There are various reports of livestock pregnancy rates of 30% to 60% when using biopsied embryos, similar to the rates obtained with intact embryos and considered sufficient for commercial applications (Agca et al, 1998, Chrenek et al 2001, Garcia, 2001, Lopes et al 2001, Park et al 2001, Chen et al 2002, Tominaga, 2004, Tominaga and Hamada, 2004.…”
Section: Introductionmentioning
confidence: 64%
“…The embryos that reached the blastocyst stage earlier were predominantly males and these male embryos had better morphology and subsequently hatched at a greater rate than female embryos. PCR analysis for sexing of in vivo produced D 7 embryos indicated that male embryos developed faster and were graded higher than female embryos (Tominaga, 2004). The sex ratio was significantly shifted to the male IVP embryos also in more recent publications (Kimura et al, 2008;Alonso et al, 2009).…”
Section: Discussionmentioning
confidence: 82%
“…The freeze-thawingbiopsy protocol rendered again, with both cryoprotectants, satisfactory pregnancy rates (about 50%). Also the ultra-rapid vitrification, using the gel-loading tip (Tominaga, 2004), is acceptable for embryos that underwent the biopsy and method is available to practical use in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Dentro de los suplementos, se sabe que las moléculas que modifican los ácidos grasos en la membrana afectan diferentes funciones estructurales, celulares e incluso vías de señalización (Spector y Yorek 1985, Talukdar y col 2005. Se ha informado que el uso de PUFA como el ácido linoleico (C18:2n-6) (Tominaga 2004), ácido araquidónico (C20:4n-6) y eicosapentaenoico (C20:5n-3) (Marques y col 2007) en los medios de cultivo han demostrado proporcionar mayor fluidez y versatilidad a las membranas (Zeron y col 2002, Spector y Yorek 1985, lo que estaría relacionado con una mejor calidad embrionaria y mayor criotolerancia (Marei y col 2010).…”
Section: Discussionunclassified